An observer tool to enhance learning of incoming anesthesia residents’ skills during simulation training of central venous catheter insertion: a randomized controlled trial - Dan Benhamou; Sarah Tant; Benoit Gille; Yannis Bornemann; Laura Ruscio; Karl Kamel; Chloé Dunyach; Bénédicte Jeannin; Maxime Bouilliant-linet; Antonia Blanié (BMC Medical Education, 2023)
Abstract Background Central venous catheter (CVC) insertion using simulation is an essential skill for anesthesiologists. Simulation training is an effective mean to master this skill. Given the large number of residents and the limited duration of training sessions, the active practice time is limited and residents remain observers of their colleagues for much of the session. To improve learning during observation periods, the use of an observer tool (OT) has been advocated but its educational effectiveness is not well defined. Methods Incoming anesthesia residents were randomized to use an OT (i.e. procedural skill-based checklist) (OT+) or not (OT-) when observing other residents during a simulation bootcamp. The primary outcome was a composite score (total 60 points) evaluating CVC procedural skills rated immediately after the training. This score covers theoretical knowledge explored by multiple choice questions (MCQs) (/20), perceived improvement in knowledge and skills (/20), perceived impact on future professional life (/10) and satisfaction (/10). Measurements were repeated 1 month later. Residents in each group recorded the number of CVCs placed and their clinical outcomes (attempts, complications) during the first month of their clinical rotation using a logbook. Results Immediately after training, the composite score was similar between the two groups: 45.3 ± 4.2 (OT+, n = 49) and 44.4 ± 4.8 (OT-, n = 42) (p = 0.323). Analysis of sub-items also showed no difference. Results at 1 month were not different between groups. Analysis of the logbook showed no difference between groups. No serious complications were reported. Conclusions The use of a procedural task-based OT by incoming anesthesia residents and used during CVC insertion simulation training was not associated with better learning outcomes, neither immediately after the session nor when re-evaluated 1 month later. The training at least once on simulator of all residents could limit the impact of OT. Further studies are necessary to define the place of OT in simulation training.